Shifting priorities of the EU as a development actor: context and consequences. Issue 4 (8th August 2021) - Hadfield, Amelia; Lightfoot, Simon
ABSTRACT: EU development policy conforms reliably to a stable and predictable policy-cycle between 1957 until the early 2000s. After that, we see a shift towards more explicitly frame-based outputs utilising the mechanism of policy nexuses. This article, drawing on a range of primary policy documents and key case studies, illustrates the difference between the first era by which EU development retains a stable process within the boundaries of the policy cycle and the subsequent shift to the use of 'framing' to bind a series of separate activities to the core of development policy via the use of 'policy nexuses'. The article concludes with reflections on the resulting seminal changes to the EU's overall approach to development, and its implications for the EU as a development actor.